Palynology of the Triassic : Jurassic of the Silves Group in Portugal, its implications on a changing world - Vilas Boas, Margarida (2023)
ABSTRACT: The biostratigraphy of the Lusitanian and Algarve basins is based on macrofossils and microfossils (foraminifers, nannofossils, and ostracods). Compared to these works, palynological studies are rare in these basins. Palynomorphs are a powerful biostratigraphic and paleoenvironmental tool, and their research could significantly contribute to the context of the two basins. In this project, the Upper Triassic and Lower Jurassic of the Lusitanian and Algarve asins were studied. In the Lusitanian Basin, twelve sections were sampled, all in Coimbra and Miranda do Corvo: Lamas I, Lamas II, Castelo Viegas I, Castelo Viegas II, IdealMed, Alto de São João, Parque de Campismo, Sobral Cid, Carvalhais, Redonda, Lordemão and Eiras. A total of 122 samples were collected in these sections and studied in detail. In the Algarve Basin, fifteen sections were sampled throughout the entire basin: Vale de Fuzeiros, Bengado, International Racetrack of Algarve, Marco, Loulé Rock Salt Mine, Santa Rita, Amorosa, Amado’s Beach, Rocha da Pena, Bodega, Barragem do Funcho, Santa Catarina Fonte do Bispo, Fonte da Pedra, Diapiro de Albufeira and Ayamonte. Full amount of 254 samples were collected in these sections and studied in detail. Six boreholes were sampled: Golfinho-1, Santiago do Cacém-3, Santiago do Cacém-42, Santiago do Cacém-61, Campelos-1, and Lula-1, performing 122 samples collected from these boreholes and studied in detail. The data obtained in the Lusitanian Basin allowed improving the dating of the units of the Silves Group, from the oldest to the most recent: Conraria Formation, Penela Formation, Castelo Viegas Formation, and Pereiros Formation. The co-occurrence of typical Norian and Rhaetian palynomorphs, such as Classopollis meyerianus, Granuloperculatipollis rudis, Patinasporites densus, Vallasporites ignacii, Duplicisporites granulatus, Paracirculina quadruplicis, and Praecirculina granifer, allowed the Conraria Formation, at the base of the Silves Group, to be dated from the Norian to lower Rhaetian. Based on the palynological content, proposing the informal Classopollis meyerianus-Granuloperculatipollis rudis palynozone for the Conraria Formation was possible. Two informal palynozones are proposed for the Pereiros Formation:Ischyosporites variegatus-Kraeuselisporites reissingeri and Pinuspollenites minimus. The informal palynozone Ischyosporites-variegatus-Kraeuselisporites reissingeri is associated with the upper Rhaetian due to the presence of Classopollis meyerianus, Classopollis torosus together with index species of this age, such as Ischyosporites variegatus, Kraeuselisporites reissingeri, and Rhaetipollis germanicus. The informal palynozone Pinuspollenites minimus is defined based in the first occurrence of Pinuspollenites minimus and Perinopollenites elatoides, accompanied by the dominance of Classopollis meyerianus and Classopollis torosus, dating from the base of the Hettangian. Therefore, based on the palynological association obtained in these two informal palynozones, it is possible to date the Pereiros Formation as being upper Rhaetian to lower Hettangian and conclude that the Triassic-Jurassic transition occurs at the base of this formation within the informal Ischyosporites variegatus- Kraeuselisporites reissingeri palynozone. The absence of palynological data from the Penela and Castelo Viegas formations due to not favorable lithologies to palynological studies did not allow for a review and improvement in the precision of the age associated with these formations. However, considering their stratigraphic position, sandwiched between the Conraria Formation (Norian – early Rhaetian) and the Pereiros Formation (late Rhaetian – earliest Hettangian), these formations would date, indirectly, from the Rhaetian. In conclusion, the palynological associations obtained in the Lusitanian Basin made it possible to date the formations of the Silves Group from the Norian to the Hettangian. To identify the limit between the Triassic and Jurassic in the Lusitanian Basin, new samples were collected in the most basal part of the Pereiros Formation. The palynological content obtained, such as the spores Calamospora tener, Ischyosporites variegatus, Kraeuselisporites reissingeri, and Porcellispora longdonensis, and the pollen grains Alisporites sp., Perinopollenites elatoides, and Pinuspollenites minimus, allowed confirming the Hettangian age for the base of this formation. The presence of foraminiferal linings in the basal part of the Pereiros Formation documents, the first marine incursion event that occurred in the Lusitanian Basin. These data allow us to interpret this unit as deposited in an estuary environment and suggest a small marine transgression episode. The middle part of this formation is interpreted as a coastal plain environment dominated by fluvial sedimentation processes recording a small marine regression episode, and the top of Pereiros Formation as an evaporite tidal flat under hot, arid climatic conditions.In the Algarve Basin, the Silves Group comprehends the units, from the oldest to the most recent: São Bartolomeu de Messines Clays, Silves Sandstones, Silves Marl-Carbonate Evaporitic Complex, and Volcano-Sedimentary Series. For the first time, it is possible to associate an age interval with the Silves Group, ranging from the early Carnian to the early Hettangian, based on palynomorphs, including the Triassic-Jurassic transition, and to establish paleoenvironmental interpretations. The most basal part of the Silves Sandstones was sampled, and its palynological association, which comprised Aulisporites astigmosus, Enzonalasporites vigens, Vallasporites ignacii, and Samaropollenites minimus, allowed the base of this unit to be dated as early Carnian. These data will enable us to interpret that the beginning of sedimentation in the Algarve Basin occurred in the Late Triassic (early Carnian). The co-occurrence of taxa such as Aulisporites astigmosus, Enzonalasporites vigens, Samaropollenites speciosus and Tulesporites briscoensis (recorded for the first time in Iberia and Europe) indicates a mixture of microfloras with affinities from Central Europe and North America, in the Carnian, this data is consistent with the paleogeographic position of the Iberian Peninsula during the Late Triassic. The new palynological data from this investigation indicate that the top of the Silves Sandstones unit dates from the late Carnian, the base of the Silves Marl-Carbonate Evaporitic Complex unit dates from the late Carnian and the top of this last unit dates from the late Rhaetian to the early Hettangian. From a paleoenvironmental point of view, the presence and rapid increase of algal spores (Plaesiodictyon mosellanum ssp. variable, Plaesiodictyon mosellanum ssp. bullatum, Botryococcus spp., and Ovoidites sp.) at the base of the Silves Marl-Carbonate Evaporitic Complex unit indicates the transition from alluvial depositional systems (Silves Sandstones) initially, to lacustrine environments, which later changed to arid coastlines. The consistent increase in xerophytic elements (e.g., pollens grains Alisporites spp., Classopollis spp., Cerebropollenites spp., and Perinopollenites spp.) indicates a shift to more arid and hot conditions for the top of the Silves Group, being consistent with lithofacies deposited in sabkha environment (evaporites). For the first time, the Triassic-Jurassic transition is described based in palynomorph studies in the Algarve Basin at the top of the Silves Marl-Carbonate Evaporitic Complex in the Loulé Rock Salt Mine. The previous transition occurs in a mudstone layer, with ca. 1 m thick, interspersed with evaporites, and should correspond to a short period of interruption of the evaporite environment. With this work, we propose an age of the Silves Group in the Lusitanian Basin, from the Norian – early Hettangian, and in the Algarve Basin from the lower Carnian to the early Hettangian, with the identification, for the first time, of the Triassic-Jurassic transition in Portugal. The new lithostratigraphic schemes of the Silves Group for the Lusitanian and Algarve basins, together with the paleoenvironmental interpretations obtained with this investigation, are a significant contribution to the context of the Late Triassic and Early Jurassic in Portugal, especially for biostratigraphy.